Escape Room in the Educational Field: Analysis of a Mathematics Classroom Practice - Moreno Lozano, Iván (2023)
Currently, both society and education are experiencing a transformational process supported by a rapid technological progress that has provided new ways of interacting and relating to each other. Regarding the evolution of education, it has involved the incursion of new teaching-learning methodologies of active character such as gamification. Thus, the main goal of this research was to present an intervention proposal based on learning through a game, specifically, an escape room framed in the mathematics field. With the above, the authors intended to observe both the progress and the acquisition of specific and cooperative academic skills by the students. Hence, through the analysis of the methodological applicability of gamification and escape room techniques in primary education, the researchers conducted an investigation based on meta-evaluation on the ontological (studied reality), epistemological (what, who, why, and why teach) and, mainly, methodological level. From the perspective of two professors with the roles of Observer 1 participant and Observer 2 external, the authors reached the following results and conclusions. First, the use of this type of methodologies positively influences the acquisition of mathematical skills. In addition, not only was there an improvement in the cooperative environment in the classroom, but also motivation was increased. Thus, it is invited to reflect on the need to continue developing pedagogical transformation actions in the classroom to adapt teaching to the demands and demands of today’s society.